Aerobic metabolism during predation by a boid snake - Canjani, C.; Andrade, D. V.; Cruz-Neto, A. P.; Abe, Augusto Shinya [UNESP] (Elsevier B.V., 2002)
We quantified the oxygen uptake rates ((V) over dot O-2) and time spent, during the constriction, inspection, and ingestion of prey of different relative sizes, by the prey-constricting boid snake Boa constrictor amarali. Time spent in prey constriction varied from 7.6 to 16.3 min, and (V) over dot O-2 during prey constriction increased 6.8-fold above resting values. This was the most energy expensive predation phase but neither time spent nor metabolic rate during this phase were correlated with prey size. Similarly, prey size did not affect the (V) over dot O-2 or duration of prey inspection. Prey ingestion time, on the other hand, increased linearly with prey size although (V) over dot O-2 during this phase, which increased 4.9-fold above resting levels, was not affected by prey size. The increase in mechanical difficulty of ingesting larger prey, therefore, was associated with longer ingestion times rather than proportional increases in the level of metabolic effort. The data indicate that prey constriction and ingestion are largely sustained by glycolysis and the intervening phase of prey inspection may allow recovery between these two predatory phases with high metabolic demands. The total amount of energy spent by B. c. amarali to constrict, inspect, and ingest prey of sizes varying from 5 to 40% of snake body mass varied inversely from 0.21 to 0.11% of the energy assimilated from the prey, respectively. Thus, prey size was not limited by the energetic cost of predation. on the contrary, snakes feeding on larger prey were rewarded with larger energetic returns, in accordance with explanations of the evolution of snake feeding specializations. (C) 2002 Elsevier B.V. All rights reserved.
Keywords: energetics; feeding; boidae; snakes; metabolism; constriction; predation; prey ingestion